Catfish Spring Roll Making Training at Yakarim Orphanage, Sidoarjo - Firmansyah, Mokhamad; Rahmawati, Nur (abdimesin, 2024)
Catfish is one of the fish that lives in Indonesian waters and contains a lot of nutrients. With a fairly affordable price, this fish is highly recommended by nutritionists because it contains Omega 3, 6, and 9, which are beneficial for children's intelligence. However, the interest of the residents, especially children, in consuming this fish is very low. This may be due to the many bones and the fishy smell of this fish. Therefore, this training activity was carried out with the aim of increasing people's interest in consuming catfish by processing it into spring rolls. This training activity used a practice-based socialization approach. The result of this study was a new idea for processing catfish into catfish spring rolls.